2020
DOI: 10.1177/1178223420977848
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of 21-Gene Recurrence Score Assay by Using Pathological and Immunohistochemical Parameters in Breast Cancer

Abstract: Background: Oncotype Dx is used to predict the long-term recurrence risk in patients with estrogen receptor (ER)-positive and human epidermal growth factor receptor 2 (HER2)-negative invasive breast cancer (BC). This study aimed at establishing a correlation between clinicopathological parameters and recurrence score (RS), subsequently improving predictability and ultimately justifying the use of the multigene assay. Materials and methods: A retrospective analysis of the pathology and clinical data of 114 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It has previously been shown to be an independent prognostic variable, with a negative PR score associated with poor prognosis [ 48 ]. We are not the first to report an association between the PR score and the RS [ [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], however the key Oncotype trials did not look at the PR score and therefore this relationship has only been shown by real world data out with clinical trial settings. We have one of the larger datasets showing this association.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown to be an independent prognostic variable, with a negative PR score associated with poor prognosis [ 48 ]. We are not the first to report an association between the PR score and the RS [ [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ], however the key Oncotype trials did not look at the PR score and therefore this relationship has only been shown by real world data out with clinical trial settings. We have one of the larger datasets showing this association.…”
Section: Discussionmentioning
confidence: 99%